Management of acute and traumatic wounds with negative-pressure wound therapy with instillation and Dwell time - Diehm, Yannick; Fischer, Sebastian; Wirth, Garrett A.; Haug, Valentin; Orgill, Dennis P.; Momeni, Arash; Horch, Raymund; Lehner, Burkhard; Kneser, Ulrich; Hirche, Christoph (Plastic and reconstructive surgery, 2021)
Background: A promising and useful development of negative-pressure wound therapy (NPWT) is the addition of instillation and dwell time of topical wound solutions (NPWTi-d). Uses of NPWTi-d include acute and traumatic wounds, whereby wound closure may be facilitated via wound cleansing and promotion of granulation tissue formation. This systematic review summarizes publications on NPWTi-d in the treatment of acute and traumatic wounds. - Methods: A systematic review was performed analyzing articles from major clinical databases. Only clinical studies ≥10 patients reporting on the application of NPWTi-d in acute and traumatic wounds were included. - Results: One hundred ninety-two articles were retrieved, of which 10 articles met inclusion criteria. Of those, 2 were lesser-quality randomized controlled trials, comparative studies or prospective cohorts, 2 were retrospective studies, and 6 retrospective cohort studies. In total, included publications reported 109 patients with acute and traumatic wounds treated with NPWTi-d. Data from these studies indicated the potential for reduction in bacterial bioburden through wound cleansing and promotion of granulation tissue formation, thereby facilitating wound closure, reduced length of therapy and hospital time. However, for most publications, different wound causes and subsequently no isolated results for acute and traumatic wounds were reported. - Conclusion: NPWTi-d has promise to be effective in facilitating wound closure and reducing the time for wound closure. The present systematic review demonstrates a relatively low level of evidence available to objectively support this effect. To underline these positive results, large prospective, randomized controlled trials are necessary to manifest the role of NPWTi-d in the daily clinical routine for this wound category.